Preferential etching by flowing oxygen on the (100) surfaces of HPHT single-crystal diamond - Yang, L.M.; Gong, J.H.; Yue, Z.M.; Liu, S.N.; Chen, Q.L.; Gao, J. (Сверхтвердые материалы, 2017)
Application of diamond is determined by its oxidation behaviour in some measure. Oxidation process of single-crystal diamond prepared under high pressure and high temperature has been studied by the thermal analysis, scanning electron microscope and Raman spectrometer. The result of a simultaneous thermal analysis indicates that single-crystal diamond is oxidized at ~ 818 °C at a heating rate of 5°C/min in the flowing oxygen. Based on the data of the thermal analysis at different heating rates, the activation energy is calculated by the Kissinger method. A weight loss rate increases with the rising heat treatment temperature from 600 to 800°C. After the oxidation at 800 °C, etch pits emerge on the {100} surfaces of single-crystal diamond, while the {111} surfaces are smooth. Shapes of the etch pits on the {100} surfaces are inverted pyramidal hollows, with edges direction parallel to the <110> direction. Застосування алмазу в якійсь мірі визначається його поведінкою при окисленні. За допомогою термічного аналізу, скануючої електронної мікроскопії і спектроскопії комбінаційного розсіювання світла вивчено процес окислення монокристалічного алмазу, отриманого при високому тиску і високій температурі. Одночасний термічний аналіз показав, що монокристалічний алмаз окислюється при ~ 818 °С при швидкості нагріву 5 °С/хв в потоці кисню. На основі даних термічного аналізу при різних швидкостях нагрівання розраховано енергію активації за методом Кіссінджера. Швидкість втрати ваги зростає з підвищенням температури термообробки від 600 до 800 °C. Після окислення при температурі 800 °С ямки травлення з’являються на поверхні {100} монокристалічного алмазу, в той час як поверхні {111} гладкі. Форма ямок на поверхнях {100} – перевернуті пірамідальні западини з ребрами в напрямку паралельному <110>. Применение алмаза в какой-то мере определяется его поведением при окислении. С помощью термического анализа, сканирующей электронной микроскопии и спектроскопии комбинационного рассеяния света изучен процесс окисления монокристаллического алмаза, полученного при высоком давлении и высокой температуре. Одновременный термический анализ показывает, что монокристаллический алмаз окисляется при ~ 818 °С при скорости нагрева 5 °С/мин в потоке кислорода. На основе данных термического анализа при различных скоростях нагрева рассчитана энергия активации по методу Киссинджера. Скорость потери веса возрастает с повышением температуры термообработки от 600 до 800 °C. После окисления при температуре 800 °С ямки травления появляются на поверхности {100} монокристаллического алмаза, в то время как поверхности {111} гладкие. Форма ямок на поверхностях {100} – перевернутые пирамидальные впадины с ребрами в направлении параллельном <110>.